Study of the Sediments of the Dam of Okpara (Benin): Physico-Chemical Characterization and Speciation of Iron and Manganese - SUANON, Fidèle (My University, 2013)
Iron and Manganese contents and parameters including pH, conductivity, and organic matter contents were determined in the sediments of the Okpara dam in Northern Benin. Fifteen samples were collected during a one-month period and analysed in laboratory using the method of sequential extraction of Tessier. The analyses indicated that sediments con- tained high concentrations in reducible fraction of Iron and relatively high contents of exchangeable fraction, acidhy- drolysable fraction and residual fraction of Manganese. The findings of this study confirmed the hypotheses that the metal contents of the sediments were relatively high and varied according to the geochemical phases.
Keywords: Sediments; Iron; Manganese; Geochemical Phases; Pollution